KINERJA REKSADANA TERPROTEKSI SYARIAH DENGAN INDEKS SHARPE, TREYNOR, DAN JENSEN (PERIODE TAHUN 2013-2016) - Anindita Maditiara; Nafik hnafik (Universitas Airlangga, 2018)
The objective of this research is to identify whether there is a difference of theperformance of mutual fund shares among Sharpe, Treynor, and Jensen Index (Period 2013- 2016) by analyzing the performance of each sampling stock from Sharia-Protected Mutual Funds. The population of this research is all Sharia-Protected Mutual Funds registered at Bapepam-LK. The data used in this research are monthly Net Asset Value (NAV), Indonesian Sharia Stock index (ISSI), and Sukuk Ijarah. The approach that has been used in this research is quantitative with One-Way Anova analysis technique with three variables Sharpe Index (X1), Treynor Index (X2), Jensen Index (X3), as variables that measure the performance of ShariaProtected Mutual Fund. REFERENCESDarmadji & Fakhruddin, 2011, Pasar Modal di Indonesia, edisi 3, Salemba Empat, Jakarta.Husnan, Suad. 2001. Dasar-dasar Teori Portofolio dan Analisis Sekuritas. Edisi II: Yogyakarta: UPP-AMP-YKPN.KEMENAG, 2016. Al-Quran dan terjemahannya. Jakarta: KEMENAGOtoritas Jasa Keuangan. 2014. Regulasi Peraturan OJK. (http://www.ojk.go.id, diakses 15 Maret 2017).Riyandono. 2008. Bursa Efek dan Investasi Syariah. Jakarta: Serambi.Rudiyanto. 2011. Reksa Dana untuk Pemula. Jakarta: Elex media KomputindoSudarsono, Heri. 2007. Bank danLembaga Keuangan Syariah (Deskripsi dan Ilustrasi). Edisi Kedua. Yogyakarta: Ekonisia.Tandelilin, Eduardus. 2001. Analisis Investasi dan Manajemen Portofolio. Yogyakarta: BPFE.Tandelilin, Eduardus. 2010. Portofolio dan Investasi. Yogyakarta: Kanisius